2010
DOI: 10.1037/a0017532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on phenomenology and consistency of flashbulb memories of September 11 and a staged control event.

Abstract: The special status of flashbulb memories was investigated by contrasting the effects of age on the phenomenology and consistency of flashbulb memories of September 11 over a 2-year delay period with those of a mundane staged control event, learning that one had not won a small prize. Flashbulb memories produced no significant age effects for either phenomenological characteristics or test-retest consistency, as predicted by Mather"s (2004) emotional compensation hypothesis. By contrast, the control event resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…This point is extremely problematic, since for private memories of mundane events no control is attainable on the individual's variability of experiences and emotional implications. Kvavilashvili, Mirani, Schlagman, Erskine, and Kornbrot (2010) used a staged event to have an autobiographical control with less variability than unspecified personal events considered in other studies, although their procedure had limited ecological validity, since the control event was not self-chosen by participants and its level of consequentiality was not comparable with the target event of a FBM. During their life, individuals form apparently stable memories of ordinary autobiographical events, which do not necessarily refer to contextual aspects of learning of important public news.…”
Section: Discussionmentioning
confidence: 98%
“…This point is extremely problematic, since for private memories of mundane events no control is attainable on the individual's variability of experiences and emotional implications. Kvavilashvili, Mirani, Schlagman, Erskine, and Kornbrot (2010) used a staged event to have an autobiographical control with less variability than unspecified personal events considered in other studies, although their procedure had limited ecological validity, since the control event was not self-chosen by participants and its level of consequentiality was not comparable with the target event of a FBM. During their life, individuals form apparently stable memories of ordinary autobiographical events, which do not necessarily refer to contextual aspects of learning of important public news.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the finding that older adults can function cognitively as well as young adults in everyday life while displaying substantial deficits in laboratory PM tasks and other cognitive tasks measuring speed of processing, working memory and long-term memory (Park, Polk, Mikels, Taylor, & Marshuetz, 2001), is important not only theoretically, but also practically due to popular culture and prevailing beliefs that cognitive functions significantly deteriorate in old age. Although the age-PM-paradox has been suggested to be unique to PM and not extend to retrospective memory in general (Phillips et al, 2008), latest findings reported in the retrospective memory literature on flashbulb memories (Kvavilashvili, Mirani, Schlagman, Erskine, & Kornbrot, 2010), memories for incidental stimuli in the environment (Qin et al, 2014) and involuntary autobiographical memories (Berntsen et al, 2017;Kvavilashvili, Niedźwieńska, & Kliegel, 2016), to name the few, suggest that the absence of age effects for naturalistic tasks may be more widespread than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a great deal of prior research exploring memory for emotional public events in young adults and healthy older adults (Berntsen & Thomsen, 2005; Bohn & Berntsen, 2007; Christianson, 1989; Davidson, Cook, & Glisky, 2006; Davidson & Glisky, 2002; Kensinger, Krendl, & Corkin, 2006; Kvavilashvili, Mirani, Schlagman, Erskine, & Kornbrot, 2010; Tekcan & Peynircioglu, 2002), but far less in patients with memory disorders like Alzheimer's disease (AD) or Mild Cognitive Impairment (MCI) (reviewed by (Broster, Blonder, & Jiang, 2012; Budson & Gold, 2009). The reported effects of AD on memory for these events are somewhat mixed, with some authors concluding that AD patients can form vivid, ‘flashbulb’ memories for these events (reviewed by (Broster et al, 2012) and others concluding that it is likely that AD patients no longer have the capacity to form flashbulb memories (reviewed by (Budson & Gold, 2009).…”
mentioning
confidence: 99%